Epidemiology of the extent of recreational noise exposure and hearing protection use: cross-sectional survey in a nationally representative UK adult population sample - Christopher J. Armitage; Michael T. Loughran; Kevin J. Munro (BMC, 2020)
Abstract Background Hearing loss is prevalent and disabling, yet little is known about the extent of recreational noise exposure and hearing protection use. The aim of the present research was to estimate the extent of recreational noise exposure and hearing protection use in a sample representative of the UK adult population. Methods We conducted a cross-sectional survey of 10,401 UK adults who were representative of the population. Results More than 7000 people (n = 7590, 73.0%) reported exposure to recreational noise excluding headphone and earphone use in the last 12 months. Just 158 people (2.1%) reported wearing hearing protection for every noisy recreational activity. Age (younger people) and beliefs of a behavioral (as opposed to genetic) cause of hearing loss were predictive of both higher recreational noise exposure and greater hearing protection use. Men were more exposed to recreational noise but women were less likely to use hearing protection. Conclusions For the first time, the present research quantifies the recreational noise exposure and low levels of hearing protection use in a representative sample of the UK population. The biggest public health gains are likely to be achieved through interventions targeted at younger people and in explaining behavioral (as opposed to genetic) causes of hearing loss.